The procedure of the judicial control on bail - Anane, Iuliana (Technium Social Sciences Journal, 2023)
Preventive measures represent a type of coercive procedural measures through which the authority’s judicial systems attempt to restrict the defendant's freedom of movement to ensure that trials criminal proceedings are carried out accordingly. From this point of view, preventive measures reach their goal the objective by interfering with the defendant's individual liberty to the minimum necessary or by his deprivation for a certain period of time. The use of bail as a preventive measure was seen as a way to avoid use measure correctional. The bond represent depositing a sum of money at the court registry by a person against whom it is in during a criminal procedure, being designed as an alternative to prison, this changing the perception of procedural institutions of judicial control on bail. The evolution of the institution led to the emergence of a new profession, that of professional guarantor, which fulfills a function similar to that of a banking service, using own funds to guarantee the release in exchange for a fee. Therefore, we must remain aware that a significant control action judicial bail will only be achieved when attention is focused on these issues important. Pretrial justice ultimately depends on reaching a tipping point which can only take place when major improvements have been shown to be necessary and feasible in the period leading up to the trial. The current bail system causes hardship to defendants and cause considerable financial costs to society.